Pengaruh Metode Reward terhadap Kedisiplinan Belajar Siswa di SMPN 1 Karawang Barat - Maulida, Najmi; Sitika, Achmad Junaedi; Nurhasan, Nurhasan; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
There is a problem with the low level of student learning discipline. This study aims to determine the significant influence between rewards on student learning discipline at SMPN 1 Karawang Barat. This research method uses quantitative research with ex post facto type. The population in this study amounted to 478 students and the number of samples taken based on the simple random sampling technique amounted to 48 students. The data analysis techniques used are validity tests, reliability tests, normality tests, linearity tests and hypothesis tests (using simple linear regression analysis, namely t-tests and coefficients of determination). The Tcalculate value > Ttabel (3.602 > 2.160) and the Sig. value is 0.001 < 0.05 meaning that H0 is rejected and Ha is accepted or there is an influence of X on Y. So it can be concluded that the answer to the problem posed is "There is an influence of the reward method on student learning discipline at SMPN 1 Karawang Barat".